Sexual Violence in the Digital Age: A Criminal Law Conundrum?. Issue 5 (August 2021) - Jurasz, Olga; Barker, Kim
Abstract: The emergence of new interactions, notably those online, has led to the parallel development of criminal behaviors—not all of which are captured by the current legal framework. This article addresses the challenge posed to criminal law by the emergence of technologically facilitated violence, specifically its sexualized online forms. In particular, it argues for cautious yet specific criminalization of violent behaviors online whilst considering the broader criminal liabilities of all actors involved in the facilitation and perpetration of digital sexual violence. This article draws upon national—contentious—examples of attempts to regulate disruptive sexual violence perpetrated through digital means, with particular attention given to provisions in the UK, Germany, and France.